A novel textile wastewater treatment using ligninolytic co-culture and photocatalysis with TiO2 - Andrea Blanco-Vargas, Christian Fernando Ramírez-Sierra, Marcela Duarte Castañeda, Milena Beltrán-Villarraga, Luz Karime Medina-Córdoba, Alex Enrique Florido-Cuellar, Jairo Armando Cardona-Bedoya, María Claudia Campos-Pinilla, Aura Marina Pedroza-Rodriguez (Pontificia Universidad Javeriana, 2018)
Textile industries produce effluent wastewater that, if discharged, exerts a negative impact on the environment. Thus, it is necessary to design and implement novel wastewater treatment solutions. A sequential treatment consisting of ligninolytic co-culture with the fungi Pleurotus ostreatus and Phanerochaete crhysosporium (secondary treatment) coupled to TiO2 /UV photocatalysis (tertiary treatment) was evaluated in the laboratory in order to discolor, detoxify, and reuse textile effluent wastewater in subsequent textile dyeing cycles. After 48 h of secondary treatment, up to 80 % of the color in the wastewater was removed and its chemical and biochemical oxygen demands (COD, and BOD5 ) were abated in 92 % and 76 %, respectively. Laccase and MnP activities were central to color removal and COD and BOD5 abatement, exhibiting activity values of 410 U L−1 and 1 428 U L−1 , respectively. Subjecting wastewater samples to 12 h of tertiary treatment led to an 86 % color removal and 73 % and 86 % COD and BOD5 abatement, respectively. The application of a sequential treatment for 18 h improved the effectiveness of the wastewater treatment, resulting in 89 % of color removal, along with 81 % and 89 % COD and BOD5 abatement, respectively. With this sequential treatment a bacterial inactivation of 55 % was observed. TiO2 films were reused continuously during two consecutive treatment cycles without thermic reactivation. Removal percentages greater than 50 % were attained. Acute toxicity tests performed with untreated wastewater led to a lethality level of 100 % at 50 % in Hydra attenuata and to a growth inhibition of 54 % at 50 % in Lactuca sativa. Whereas sequentially treated wastewater excreted a 13 % lethality at 6.25 % and an inhibition of 12 % at 75 % for H. attenuata and L. sativa, respectively. Finally, sequentially treated wastewater was reused on dyeing experiments in which 0.86 mg g−1 adsorbed dye per g of fabric, that is equivalent to 80 % of dye adsorption.